1997
DOI: 10.1038/sj.ejcn.1600454
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal development and tracking of calcium and dairy intake from teenager to adult

Abstract: Objectives: Because of growing interest in the potential role of calcium in preventive pediatric strategies against osteoporosis, the longitudinal development and tracking of calcium and dairy intake from adolescence into adulthood was addressed. Design: In the Amsterdam Growth and Health Study, a group of 84 males and 98 females were followed over a 15 y period from age 13±27 y. The calcium and dairy intake was assessed six times by a cross-check dietary history method. To assess tracking, two traditional app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 11 publications
1
31
0
1
Order By: Relevance
“…The percentages of those in the lowest quartiles of intake at baseline who remained in that quartile at 6 years follow-up were 63.2% and 68.4% (for males) and 69.6% and 56.5% (for females) for cheese and milk and milk products respectively. Similarly, the percentages of those in the highest quartiles of intake at baseline who remained in that quartile at 6 years follow-up were 50% and 57.9% (for males) and 50% and 27.3% (for females) for cheese and milk and milk products respectively [40]. After 12 years follow-up, most of these relationships weakened but the percentages remained above 25% (the proportion expected by chance) and in the case of females in the lowest quartile of intake for cheese at baseline, the proportion remaining in this quartile increased to 75% [40].…”
Section: Maintenance Of Relative Position -Dietary Intakementioning
confidence: 91%
See 2 more Smart Citations
“…The percentages of those in the lowest quartiles of intake at baseline who remained in that quartile at 6 years follow-up were 63.2% and 68.4% (for males) and 69.6% and 56.5% (for females) for cheese and milk and milk products respectively. Similarly, the percentages of those in the highest quartiles of intake at baseline who remained in that quartile at 6 years follow-up were 50% and 57.9% (for males) and 50% and 27.3% (for females) for cheese and milk and milk products respectively [40]. After 12 years follow-up, most of these relationships weakened but the percentages remained above 25% (the proportion expected by chance) and in the case of females in the lowest quartile of intake for cheese at baseline, the proportion remaining in this quartile increased to 75% [40].…”
Section: Maintenance Of Relative Position -Dietary Intakementioning
confidence: 91%
“…Similarly, the percentages of those in the highest quartiles of intake at baseline who remained in that quartile at 6 years follow-up were 50% and 57.9% (for males) and 50% and 27.3% (for females) for cheese and milk and milk products respectively [40]. After 12 years follow-up, most of these relationships weakened but the percentages remained above 25% (the proportion expected by chance) and in the case of females in the lowest quartile of intake for cheese at baseline, the proportion remaining in this quartile increased to 75% [40]. In the Cardiovascular Risk in Young Finns Study, Mikkila et al (2005) used Principal Components Analysis to derive dietary patterns with "pattern 1" characterised by positive correlations with intakes of rye, potatoes, milk, butter, sausages and coffee but negative correlations with intakes of fruit, berries and other dairy products.…”
Section: Maintenance Of Relative Position -Dietary Intakementioning
confidence: 91%
See 1 more Smart Citation
“…There is some evidence to suggest that dietary habits learnt in infancy can influence preferences and practices in later life, and further evidence suggests fair to moderate tracking of food habits from childhood to adolescence 11 -13 . Data on tracking of nutrient intakes are variable; however, this could be partly due to the problematic issue of dietary assessment methodologies 14,15 . One study investigating the tracking of food intake patterns, including fruit and vegetable consumption, over a 6-year period from childhood to adolescence reported maintenance of dietary patterns into adolescence and concluded that efforts to promote a healthy diet should start in childhood 11 .…”
mentioning
confidence: 99%
“…A one-time assessment of dairy product intake does not predict intake over very long follow-ups, as was shown in the Amsterdam Growth and Health Study in which Ca and dairy product intake was studied six times over 15 years from age 13 to 27 years. The predictability of Ca intake over time was not sufficiently strong to identify teenagers who are likely to maintain an inadequate Ca intake in adulthood (39) . Therefore, predicting fracture risk based on adolescence dietary behaviour seems rather difficult, if not impossible.…”
Section: Dairy Products and Fracture Risk In Children And Adolescentsmentioning
confidence: 99%